Expectation of administering the first aid for traumatic victims during the absence of pre-hospital service - Fitri Anita; Tita Hariyanti; Tony Suharsono (International Journal of Public Health Science (IJPHS), 2021)
Traffic incidents become typical cases of trauma outside of hospitals. The integrated-emergency nursing system outside of hospitals becomes an important component to minimize any worsening condition of the traumatic victims. However, this pre-hospitalized service system has not been formally established in several cities or municipalities. This research aims to explore various hopes of the trauma-victim aid process in a region that has not applied pre-hospitalized emergency service formally. This research was carried out by implementing a qualitative research method and a case study approach to identify the themes. The research was conducted in Konawe municipality, from February until March 2020. It was done by interviewing eight participants consisting of the citizens, traffic police officers, hospital party, and health agency. Four themes result from this research. Establishing the pre-hospitalized emergency service, socializing the first aid for the incident victims, training dealing with the first aid of taking care of trauma victims, and promoting socialization for all citizens about the emergency numbers of health service institutions which could be immediately contacted when an accident occurs. There is a need for an emergency service system establishment and development.